Investigating the relationship between domestic violence with substance abuse and suicide resilience in mothers with disabled children - Mohammadi, Fateme; Barati, Majid; Borzou, Seyed Reza; Ezati, Elahe; Mohammadi, Khadejeh; Mohammadi, Zahra; Khazaei, Salman; Masoumi, Seyedeh Zahra (Frontiers in Public Health, 2023)
Introduction Mothers with disabled children are among the most critical groups exposed to domestic violence. Although domestic violence strongly affects these mothers’ physical and mental health, it subsequently affects their drug addiction and resilience to suicide. Based on this, it is crucial to investigate domestic violence, drug addiction, and resilience against suicide in mothers with disabled children. This study investigated the relationship between domestic violence, substance dependence, and resilience against suicide in mothers with disabled children in Iranian society. Methods From January to April 2023, a cross-sectional study was conducted in central and western Iran with the participation of 267 mothers with disabled children. The mothers of disabled children were selected through convenience and snowball sampling. Then they completed questionnaires included domestic violence, substance dependence and resilience against suicide. The collected data were analyzed using SPSS version 22 with descriptive statistics, such as prevalence, percentage, mean, and standard deviation, and expository measurements, including ANOVA, independent t, and regression tests. Results The study revealed that there was a strong direct correlation between domestic violence and substance abuse (r = 0.89, p < 0.001), as well as a strong indirect correlation between domestic violence and suicide resilience (r = −0.90, p < 0.001). Additionally, substance abuse and suicide resilience were negatively correlated (r = −0.93, p < 0.001). Other variables, such as the severity of children’s disability, education, financial status, and the fathers’ involvement, were predictors of domestic violence, accounting for 73.28% of the variance. Conclusion Mothers with disabled children reported moderate levels of domestic violence, which strongly impacts their physical and mental well-being, leading to drug dependency and suicide. So, it is essential to implement comprehensive planning and provide extensive support to reduce domestic violence against them. By doing so, we can enhance their physical and mental health and ultimately improve their overall quality of life.